Trends and Distribution Pattern of forests in Himachal Pradesh - Mahajan, P. K.; Dhall, S. P. (Indian Forester, 2002)
This study highlights the fact that the trends in the area under forest are not regular though the increase in the forest area in Himachal Pradesh was observed to be about 77 percent over the 17 years period ranging from 1979-80 to 1995-96. Almost perfect positive correlation is noted between change in ’total forest area’ and ’protected forest area’ when the effects of the variables such as ’reserved forest area’, ’unclassified forest area’, ’forest area not under the control of Forest Department’ have been eliminated.